Efecto de los sistemas de labranza con mecanización y tipos de fertilización en el cultivo de maíz INIAP H-554 sobre las propiedades físicas del suelo y su rendimiento productivo - Hidalgo Nata, Franklin Daniel (2021)
The management of both edaphic and foliar fertilization, as well as its application according to the changes generated by the mechanization of the soil are determining factors of corn production. Considering the above, the present research aimed to evaluate the effect of the mechanization and fertilization of corn on the physical properties of the soil and yield. The test was carried out in the Soil Department of the National Institute for Agricultural Research (INIAP), located at km. 5.5 of the Quevedo - El Empalme road. Three factors were studied: Factor A: Edaphic fertilization (A1: Without edaphic fertilization, A2: N-P-K and A3: Complete fertilization); Factor B: Tillage (B1: Without tillage and B2: With tillage) and Factor C: Foliar fertilization (C1: Without foliar fertilization and C2: With foliar fertilization), under a randomized complete block design with 2x2x3 factorial arrangement in three repetitions. The results obtained showed the physical properties of the soil prior to tillage, they were homogeneous in almost all depths, with apparent density between 0.79 and 1.32 g cm-3, real density of 2.24 and 2.96 g cm-3, and porosity between 46.28 and 58.95%. At the end of the trial, with tillage, the apparent density was modified between -0.05 and 0.02 g cm-3, the real density between -0.01 and 0.04 g cm-3, and the porosity showed changes between -0.73 and 2.97%, with respect to the untilled soil. The depth 0-10 showed higher moisture content (39.48%), while, in the following four profiles, between 0.01 and 0.91% more moisture was recorded than in the absence of tillage, while in the presence of tillage there was a higher percentage of plants with root lodging (4.78%). Both the edaphic and foliar fertilization enhanced the crop yield, while without mechanization a higher yield was obtained, so that, by combining the three factors, with complete fertilization in the absence of mechanization and with foliar fertilization, the yield reached up to the 3799.38 kg ha-1 (83.59 qq ha-1). All treatments registered economic losses except for Complete + without mechanization + with foliar fertilization, with 7.33%, followed by the N-P-K + treatment without mechanization + with foliar fertilization, with 5.46%. Keywords: lodging, complete fertilization, soil tillage, yield.